2021
DOI: 10.1021/acs.jpcc.1c05493
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Capacitive and Diffusion-Controlled Charge Storage from 3D Bulk to 2D Layered Halide Perovskite-Based Porous Electrodes for Efficient Supercapacitor Applications

Abstract: Hybrid perovskites have been widely used in solar cells and light-emitting diode applications due to superior optoelectronic properties. However, ion migration in these materials causes photo- and thermal instability. On the other hand, mixed electronic–ionic conduction could be advantageous in electrochemical energy storage applications. We have fabricated porous electrodes from three-dimensional (3D) bulk and 2D layered perovskite single crystals and demonstrated that the ion migration could play a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 140 publications
(102 citation statements)
references
References 53 publications
2
100
0
Order By: Relevance
“…One of the major discussions about perovskite-based devices is ion migration through perovskite active layer. It has been observed that ion migration in these devices is unpredictable due to various intrinsic as well as extrinsic parameters affecting ion kinetics, such as perovskite [21] Copyright 2021, American Chemical Society.…”
Section: Photorechargeable Energy Storagementioning
confidence: 99%
See 4 more Smart Citations
“…One of the major discussions about perovskite-based devices is ion migration through perovskite active layer. It has been observed that ion migration in these devices is unpredictable due to various intrinsic as well as extrinsic parameters affecting ion kinetics, such as perovskite [21] Copyright 2021, American Chemical Society.…”
Section: Photorechargeable Energy Storagementioning
confidence: 99%
“…[ 18,19 ] In this direction, MHP materials are used in lithium‐ion batteries (LIBs), photorechargeable batteries (PRBs), and ESCs. [ 20–22 ] Typical stumbling blocks of rechargeable batteries are slow charging rate and low power density, while capacitors have low energy density than batteries. ESCs are the alternative energy storage sources with high power density and decent energy density as well as fast charging rate.…”
Section: Metal Halide Perovskite Supercapacitorsmentioning
confidence: 99%
See 3 more Smart Citations